Evaluation of nutrition status of very preterm infants in neonatal intensive care units using different growth indicators. (2nd August 2021) - Wang, Na; Zhang, Jia; Yu, Zhangbin; Tang, Bin; Zhang, Lin; Yin, Yujie; Wang, Zengqin; Li, Shuangshuang; Jiang, Shanyu; Hou, Weiwei; Gao, Yan; Wang, Huaiyan; et al.
Abstract: Background: Nutrition status of very preterm infants in the neonatal intensive care unit (NICU) is strongly associated with postnatal growth. This study aimed to develop indicators of nutrition status using growth data of very preterm infants during hospitalization. Methods: The data of 596 newborns from eight NICUs were retrospectively analyzed. Inclusion criteria were birth at <32 weeks' gestation, NICU admission ≤24 h after delivery, and length of hospital stay ≥28 days. Three indicators were evaluated: (indicator I) prevalence of extrauterine growth restriction (EUGR); (indicator II) z ‐score for change in weight from birth to discharge, adjusted for birth weight z ‐score and gestational age; and (indicator III) change in weight z ‐score from birth to discharge, adjusted for birth weight z ‐score, gestational age, and time to regain birth weight. Using data from NICU 1 as the reference for the latter two indicators, we established linear regression models of the adjusted change in weight z ‐score from birth to discharge. The difference between the observed value and the baseline value (calculated by the two models) served as the nutrition indices. Results: The prevalence of EUGR differed significantly between the eight NICUs ( P = .009). Statistically significant differences were found between the mean indices calculated by the other two models (all P < .05). Conclusions: Indicator III, change in weight z ‐score from birth to discharge (adjusted for birth weight z ‐score, gestational age, and time to regain birth weight), appears to be the most accurate for evaluating the quality of nutrition in the NICU.